Critical Discourse Analysis of News on the Implementation of Mental Revolution in Law Enforcement (Oratio Directa, 2018)
This study examines how Merdeka.com and Kompas.com constructed news about the implementation of the Mental Revolution in law enforcement. Using Norman Fairclough’s critical discourse analysis, the research evaluates textual representation, discourse practice, and social practice across seven groups of news concerning publik officials, government policy, and law-enforcement cases. Interviews with editorial representatives and supporting observations were used to interpret each outlet’s framing. The analysis indicates that Merdeka.com tended to employ more explicit criticism and attribution of responsibility, whereas Kompas.com generally emphasized clarification, procedural context, and cautious language. These differences demonstrate how editorial orientation shapes publik meaning concerning accountability and law enforcement.
Keywords: Mental Revolution; Press; Law Enforcement; Critical Discourse Analysis; Online News